(3eSGdc GdMfaG aj hGdOj GdeUWais - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai (B"(3eSCdI GdMce aj CHhj GdfHj Udi Gddg Ydjg hSde CfgeG fGLjGf hdjSG aj GdfGQ UQM HPdc LejY GdYdeGA hdge aj JbQjQ Pdc eSGdcs
(3BNQgG (B:s
(3bGd GdEeGe ehab GdOjf Hf bOGeI GdMfHdj aj GdebfY hef bPa CLOGO GdfHj Udi Gddg Ydjg hSde bJd eSdeG cGf Ch cGaQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 1663s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs